Distribution and Toxicity Assessment of Horseshoe Crabs, Tachypleus gigas and Carcinoscorpius rotundicauda at Pasir Putih Village, Kuching, Sarawak - Lim, Kim Yong (Universiti Malaysia Sarawak (UNIMAS), 2017)
The study focuses on the distribution and toxicity of horseshoe crabs, Tachypleus gigas and Carcinoscorpius rotundicauda in a beach off Pasir Putih Village. A total of 140 T. gigas and 24 C. rotundicauda were caught throughout the sampling period from August to December. Environmental factors such as physico-chemical parameters and sediment distribution were analysed to correlate with the distribution of the two species which the sediment is dominated by silt and clay for seaward transects. The carapace width, total length, telson length and body weight of the two species were recorded for distribution studies. Out of the 75 female samples, 39 egg samples and 23 samples out of all samples with soft tissue and eggs were assessed by using high performance liquid chromatography (HPLC) for PSP and TTX respectively. The PSP content detected were ranging from 2246.94 - 132913.74 µg eq.STX/kg (n= 23) while the TTX content were found only in soft tissue of T. gigas ranging from 0.56 - 126.40 MU/g (n = 6). The PSP content had exceeded the Malaysian regulatory limit of 80µg eq.STX/kg while the soft tissue that contained 126.40 MU was considered moderately toxic which is not suitable for human consumption.